Human errors and corresponding risks in reinforced concrete bridges - Galvão, Neryvaldo (2018)
Kuala Lumpur 2018: Engineering the Developing World - Report. All rights reserved. Concerning the bridges failures that have been arising over the years, experts have pointed out as the principal cause of failure the human errors that usually take place in the design, construction and operation stages. The main goal of this paper is the identification of the design and construction errors that represent a higher risk for reinforced concrete bridges. Therefore, a human error survey was developed together with design and construction experts on this subject, to collect and assess these errors by using risk-based indicators (probability of occurrence and consequences). The corresponding survey results, given by design and construction experts, are analysed by using a decision-making tool, named Analytic Hierarchy Process (AHP), which will allow the identification of the errors with higher consequences and a higher probability of occurrence. Based on this survey, a qualitative risk-based evaluation of the errors is also performed.